Uncertainty in MMP Prediction from EOS Fluid Characterization - Dzulkarnain, Iskandar (2011)
Published results on modelling crude oils by equation of states (EOS) showed the importance of tuning the equation to fit experimental data closely. Usually various parameters relating to C7+ such critical properties are altered to obtain an equation with a high regression correlation. Although current oil samples may be analysed up to C60+, the presence of isomers for each component may still cause a high degree of uncertainty in the averaged properties. The use of different tuning factors can also cause variations in the equation of states. In practice, the fluid model after tuning does not always give good prediction for all properties. For example, a good fit for saturation pressure and viscosity may give considerable difference in the density prediction. Another set of tuning may be excellent for another property and poor fit for another. Since the prediction of the minimum miscibility pressure (MMP) depends on the EOS model, variations in the model will result in differences in the MMP value. Therefore the priority set on each property during tuning may result in widely differing MMP values.